INNOVATIVE FACILITATION OF HALAL CERTIFICATION FOR MSMES IN BANDUNG CITY: THE ROLE OF DATA-DRIVEN POLICIES AND LOCAL GOVERNMENT SUPPORT (Al-Mubin, 2024)
Halal certification for micro, small, and medium enterprises (MSMEs) has become increasingly important because it is closely linked to regulatory compliance, consumer trust, and business competitiveness. In Bandung City, however, facilitation outcomes have not yet matched the scale of policy targets, indicating a gap between program design and implementation. This study examines the role of data-driven policy and local government support in accelerating halal certification facilitation for MSMEs in Bandung City. The analysis draws on the perspectives of data-driven decision-making, public service innovation, and policy implementation. The study employs a qualitative approach with a case study design, supported by document analysis and secondary data derived from Bandung Open Data, local government planning documents, official publications of BPJPH and the Ministry of Religious Affairs, and relevant halal certification regulations. The findings show that data have been incorporated into planning and targeting, yet they still function more as an administrative base than as a precise intervention tool. Local government support is present, but its integration remains insufficient, which contributes to the persistent gap between certification targets and implementation outcomes